The first case of COVID-19 in Far Western Province of Nepal - Kamar, Sher Bahadur; Sharma, Nirajan Data; Pandey, Santosh; Shahi, Ramesh; Joshi, Jagadish; Mishra, Pradip; Pandey, Hem Raj; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2020)
Recently emerged worldwide public health problem coronavirus disease (COVID-19) is an infectious disease caused by a severe acute respiratory syndrome coronavirus 2(SARS Cov-2); end of 2019 it was identified as the cause of a cluster of pneumonia cases in Wuhan, a city in the Hubei Province of China. It rapidly spread, resulting in an epidemic throughout China, followed by pandemic throughout the world as well as in Nepal. Finally far western province became the fourth case of Nepal and index case of this province. A 34 year old male presented Seti Provincial hospital fever clinic with the complaints of fever, cough, sore throat and history of travel from Dubai to Nepal. He was kept in isolation and throat swab result was positive for SARS CoV-2. Other systemic examination and routine investigation were within normal. Course of illness was uneventful and managed conservatively. First, second and third RT-PCR became positive and fourth and fifth turned into negative and discharged at the 29th day of admission.